Research of the use of silver nanowires as a current spreading layer on vertical-cavity surface-emitting lasers - 郭霞 史磊 李冲 董建 刘白 胡帅 何艳 (Chinese physics B, 2016)
Silver nanowire（AgNW） film was proposed to apply on the surface of the vertical-cavity surface-emitting lasers（VCSELs） with large aperture in order to obtain a uniform current distribution in the active region and a better optical beam quality.Optimization of the AgNW film was carried out with the sheet resistance of 28.4 Ω/sq and the optical transmission of 94.8% at 850 nm.The performance of VCSELs with and without AgNW film was studied.When the AgNW film was applied to the surface of VCSELs,due to its better current spreading effect,the maximum output optical power increased from 23.4 mW to 24.4 mW,the lasing wavelength redshift decreased from 0.085 nm/mA to 0.077 nm/mA,the differential resistance decreased from 23.95 Ω to 21.13 Ω,and the far field pattern at 50 mA decreased from 21.6° to 19.2°.At the same time,the near field test results showed that the light in the aperture was more uniform,and the far field exhibited a better single peak characteristic.Various results showed that VCSELs with AgNW on the surface showed better beam quality.